IMPLEMENTASI MAPPING OTOMATIS DARI DATABASE MYSQL 5.6 KE PROTEGE 4.3 DENGAN TURTLE ONTOLOGY, D2RQ, JENA, DAN NETBEANS 7.4 - Widiatminingsih Widiatminingsih; Herlina Jayadianti; Heru Cahya Rustamaji (Seminar Nasional Informatika (SEMNASIF), 2017)
The problem of changing  information into the level of knowledge is still being a big problem. Manualy mapping process  from MySql to protege is still running by user/ programmers if they wants to build web  3.0 generation. This is a waste of time. By using D2Rq Turtle the transfer process from information into the form of knowledge becomes faster.